Special considerations for medical management post supraglottoplasty in various clinical contexts - Qadadha, Yazeed M.; Kille, Tony L.; Puricelli, Michael D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Laryngomalacia is the most common cause of stridor in the pediatric population. A subset of patients with laryngomalacia ultimately require surgical repair in the form of supraglottoplasty. Variability exists not only in surgical technique but also in the post operative medical management regimen. By reviewing the existing literature, we aim to summarize unique clinical contexts that should be considered and that necessitate modifications to medical management post operatively for optimal healing and outcomes.